SAHA-coupled biocompatible cellulose-based nanoparticles as HDAC-inhibitory drug delivery systems with slow and sustained release behavior - Lennart Hendrik Skodda; Maria Nußpicker; Anika Lins; Robert Klaus Hofstetter; Laura Klement; Veronika Grassl; Jan Westhoff; Marco Fortmann; Andreas Koschella; Maren Godmann; Dagmar Fischer; Carsten Hoffmann; et al. (Carbohydrate Polymers, 2026)

Winter wheat yield responses to extreme heat in the North China Plain: GGCMI-AgMIP model evaluation and a heat-stress phenology improvement in JULES-crop - Lirong You; Karina Bett-Williams; Stephen Sitch; Christoph Müller; Huiyi Yang; Jefferson Goncalves De Souza; Munir Hoffmann; Maria Carolina Duran Rojas; Beiyao Xu (Agricultural and Forest Meteorology, 2026)

Improved antioxidant activity, phenolic and volatile profiles of tropical Syrah wines aged with oak chips - Camila Maria Hoffmann; Juliane Elisa Welke; Karolina Cardoso Hernandes; Aline Camarão Telles Biasoto; Deborah dos Santos Garruti; Ídila Maria da Silva Araújo; Claudia Alcaraz Zini (Food Bioscience, 2026)

An ensemble-forecasting model for airborne grass pollen at three climatically distinct sites - Maria P. Plaza; Jose Oteros; Vivien Leier-Wirtz; Athanasios Charalampopoulos; Carmen Galán; Caroline Holzmann; Franziska Kolek; Despoina Vokou; Claudia Traidl-Hoffmann; Stefanie Gilles; Athanasios Damialis (Environmental Research, 2026)

Self-imposed time-out by rats - Fernanda Bordignon-Luiz; Guilherme Lauro Hoffmann; Maria Helena Leite Hunziker (Behavioural Processes, 2026)

Analysing the structure of antibodies using circular dichroism with an antibody augmented reference set and the algorithm SELCON - Søren Vrønning Hoffmann; Maria G. Bruque; Nykola C. Jones; Alison Rodger; Jean Aucamp; Tim R. Dafforn; Owen R. T. Thomas (European Biophysics Journal, 2026)

Transcriptome alteration induced by desiccation stress in Salmonella enterica subsp. enterica serovar Agona - Sultana Solaiman; Ellie Meeks; Ian Hines; Jie Zheng; Maria Hoffmann (Food Research International, 2025)

Extreme temperatures, recent warming and seasonal influenza-linking human exposures to respiratory health in southern Germany - Matteo Boser; Daria Luschkova; Monika Seemann; Monika Seemann; Gertrud Hammel; Anna Lang; Julia Sander; Iñaki Soto Rey; Markus Wehler; Katharina Zeiser; Claudia Traidl-Hoffmann; Maria P. Plaza (International Archives of Occupational and Environmental Health, 2025)
Purpose In the context of climate change, extreme ambient temperatures pose a major threat to human health. This study aims to provide detailed insights into how extreme temperatures and potential confounders affect respiratory morbidity. Methods We employed a 14-year time series analysis (2006–2019) in southern Germany, applying penalized distributed lag non-linear models to estimate exposure–response relationships between extreme temperatures and respiratory health outcomes, considering emergency outpatient treatments and hospital admissions at the emergency department of the University Hospital Augsburg. We thereby explored the roles of relative humidity and seasonal influenza as potential confounders and vulnerabilities related to age and gender. Results We found significantly elevated relative risks (RRs) for the short-term cumulative effect (Lag: 0–3 days) of extreme heat and the long-term cumulative effect (Lag: 0–21 days) of extreme cold on outpatient treatments and hospital admissions. Seasonal influenza was identified as a significant confounder, with attributable fractions comparable to those of cold temperatures. A sub-period analysis (2006–2012 and 2013–2019) revealed a correlation between the recent rise in temperature and the strong increase in the estimated short-term cumulative effect of extreme heat on hospital admissions (2006–2012, RR: 1.08 (95%CI [0.91, 1.27]) vs. 2013–2019, RR: 1.32 (95%CI [1.15, 1.51]). Conclusion Our study demonstrated that extreme temperatures significantly affect respiratory morbidity, with notable influences from seasonal influenza. Sub-period analysis indicated that rising temperatures are already translating into measurable effects on respiratory health, foreshadowing the potentially devastating impacts of global warming on human health. Our results thereby provide highly relevant insights to support targeted public healthcare interventions.

Unveiling hidden allergenic hotspots: A fine-scale, parameter-optimized approach for spatiotemporal mapping of urban allergenicity assessments - Carolin Trost; Thomas Rötzer; Claudia Traidl-Hoffmann; Maria P. Plaza (Sustainable Cities and Society, 2025)

A multi-scale analysis of airborne Alternaria spore dispersal: influence of meteorology, land cover and air pollution - Maria P. Plaza; Jose Oteros; Vivien Leier-Wirtz; Franziska Kolek; Annette Menzel; Jeroen T.M. Buters; Claudia Traidl-Hoffmann; Athanasios Damialis (Agricultural and Forest Meteorology, 2025)

Harnessing methods, data analysis, and near-real-time wastewater monitoring for enhanced public health response using high throughput sequencing - Padmini Ramachandran; Tunc Kayikcioglu; Tamara Walsky; Kathryn Judy; Jasmine Amirzadegan; Candace Hope Bias; Bereket Tesfaldet; Maria Balkey; Dietrich EppSchmidt; Hugh Rand; James Pettengill; Sandra Tallent; et al. (Environmental Research, 2025)

Ultrasonography Is a Valuable Tool for Assisting in Marine Fish Reproduction: Applications in Brazilian Sardine (Sardinella brasiliensis) and Lebranche Mullet (Mugil liza) - Liseth Carolina Perenguez Riofrio; Sabrina Lara da Luz; Ingrith Mazuhy Santarosa; Maria Alcina de Castro; Everton Danilo dos Santos; Leticia Cordeiro Koppe de França; Karinne Hoffmann; Marco Shizuo Owatari; Aline Brum; Caio Magnotti (Fishes, 2025)
Urogenital cannulation is a traditional method used in aquaculture to achieve sexual differentiation, but it is considered invasive. Ultrasonography is a valuable non-invasive tool for determining sex and gonadal development in fish species like mullet (Mugil liza) and Brazilian sardine (Sardinella brasiliensis) that lack sexual dimorphism. The methodology involves emitting high-frequency sound waves (20 MHz to 20,000 MHz) above the human hearing range. These waves interact with the tissues of the body, producing echoes that are detected by a transducer. The echoes are then processed by computer graphics to generate detailed images of the internal structures of the organism. This allows for the determination of the sex of fish based on the sonographic features of the tissues. For instance, in male fish, hypoechogenic structures reflect fewer sound waves, leading to darker images. Conversely, in female fish, hyperechogenic tissues reflect more sound waves, resulting in lighter images. It is possible to classify the gonadal maturation stage based on differences in image texture. This non-invasive method eliminates the need for specimen dissection. It is especially valuable when the goal is to preserve the spawners’ life and integrity. This review emphasizes the application of this technology in aquaculture, specifically targeting fish from the Clupeidae and Mugilidae families.

Identification of volatile organic compounds in purple and white soybean flowers by HS-SPME/GC-MS - Suelen Pereira Magalhães; Jaqueline Munise Guimarães da Silva; José Perez da Graça; Estela de Oliveira Nunes; Guilherme Julião Zocolo; Clara Beatriz Hoffmann-Campo; Maria Luiza Zeraik (Natural Product Research, 2025)

Temporal dynamics of Escherichia coli O157:H7 transcriptomes on the surface of shredded lettuce - Sultana Solaiman; Victor Jayeola; Ian Hines; Ellie Meeks; Jie Zheng; Maria Hoffmann (Food Control, 2025)

Reaping what we sow: Centering values in food systems transformations research - O. Care; Julie G. Zaehringer; Michael J. Bernstein; Mollie Chapman; Cecilie Friis; Sonia Graham; L. Jamila Haider; Mónica Hernández-Morcillo; Harry Hoffmann; Maria Lee Kernecker; Hannah Pitt; Verena Seufert (Ambio, 2025)
In many transdisciplinary research settings, a lack of attention to the values underpinning project aims can inhibit stakeholder engagement and ultimately slow or undermine project outcomes. As a research collective (The Careoperative), we have developed a set of four shared values through a facilitated visioning process, as central to the way we work together: care, reflexivity, inclusivity, and collectivity. In this paper, we explore the implications of a values-centered approach to collaboration in food system transformation research. The paper presents two cases that illustrate how researchers might approach centering values in practice. Where much research on food system transformation focuses on values of food system stakeholders, we contribute insights into the values of researchers in such transdisciplinary endeavors. Specifically, we argue that researchers working on sustainability transformations need to be better prepared to engage in such reflections and aspire to embody values aligned with the transformations they seek to research.

Sintered glass filter as a membrane impregnated with g-C3N4 and AuAg/g-C3N4 to degrade Rhodamine B with application in decentralized areas - Leticia Santamaría; Lyda Patricia Sabogal-Paz; Bárbara Luíza Souza Freitas; Maria Teresa Hoffmann; David Royo-Pareja; José M. López-de-Luzuriaga; Miguel Monge (Journal of Water Process Engineering, 2024)

Effects of Crotalaria spectabilis extract in Meloidogyne javanica and Heterodera glycines soybean nematodes - Tamires Scupinari; Helena Mannochio-Russo; Gustavo Galo Marcheafave; Vanderlan da Silva Bolzani; Estela de Oliveira Nunes; Waldir Pereira Dias; Clara Beatriz Hoffmann-Campo; Maria Luiza Zeraik (European Journal of Plant Pathology, 2024)

Weight of evidence evaluation of the metabolism disrupting effects of triphenyl phosphate using an expert knowledge elicitation approach - Claire Beausoleil; Anne Thébault; Patrik Andersson; Nicolas J. Cabaton; Sibylle Ermler; Bernard Fromenty; Clémentine Garoche; Julian L. Griffin; Sebastian Hoffmann; Jorke H. Kamstra; Barbara Kubickova; Virissa Lenters; et al. (Toxicology and Applied Pharmacology, 2024)

Continental-scale evaluation of downy birch pollen production: Estimating the impacts of global change - Surendra Ranpal; Susanne von Bargen; Stefanie Gilles; Daria Luschkova³; Maria Landgraf; Pawel Bogawski; Claudia Traidl-Hoffmann; Carmen Büttner; Athanasios Damialis; Markus Fritsch; Susanne Jochner-Oette (Environmental Research, 2024)

Non-animal protein hydrolysates from agro-industrial wastes: A prospect of alternative inputs for cultured meat - Bárbara Flaibam; Marcos F. da Silva; Allan H. Félix de Mélo; Priscila Hoffmann Carvalho; Fabiana Galland; Maria Teresa Bertoldo Pacheco; Rosana Goldbeck (Food Chemistry, 2024)

A multitaxonomic assessment of Natura 2000 effectiveness across European biogeographic regions - Lorenzo Ricci; Michele Di Musciano; Francesco Maria Sabatini; Alessandro Chiarucci; Piero Zannini; Roberto Cazzolla Gatti; Carl Beierkuhnlein; Anna Walentowitz; Alexandra Lawrence; Anna Rita Frattaroli; Samuel Hoffmann (Conservation Biology, 2024)
The Natura 2000 (N2K) protected area (PA) network is a crucial tool to limit biodiversity loss in Europe. Despite covering 18% of the European Union's (EU) land area, its effectiveness at conserving biodiversity across taxa and biogeographic regions remains uncertain. Testing this effectiveness is, however, difficult because it requires considering the nonrandom location of PAs, and many possible confounding factors. We used propensity score matching and accounted for the confounding effects of biogeographic regions, terrain ruggedness, and land cover to assess the effectiveness of N2K PAs on the distribution of 1769 species of conservation priority in the EU's Birds and Habitats Directives, including mammals, birds, amphibians, reptiles, arthropods, fishes, mollusks, and vascular and nonvascular plants. We compared alpha, beta, and gamma diversity between matched selections of protected and unprotected areas across EU's biogeographic regions with generalized linear models, generalized mixed models, and nonparametric tests for paired samples, respectively, for each taxonomic group and for the entire set of species. PAs in N2K hosted significantly more priority species than unprotected land, but this difference was not consistent across biogeographic regions or taxa. Total alpha diversity and alpha diversity of amphibians, arthropods, birds, mammals, and vascular plants were significantly higher inside PAs than outside, except in the Boreal biogeographical region. Beta diversity was in general significantly higher inside N2K PAs than outside. Similarly, gamma diversity had the highest values inside PAs, with some exceptions in Boreal and Atlantic regions. The planned expansion of the N2K network, as dictated by the European Biodiversity Strategy for 2030, should therefore target areas in the southern part of the Boreal region where species diversity of amphibians, arthropods, birds, mammals, and vascular plants is high and species are currently underrepresented in N2K.

Thermodynamic assessment of a large-scale magnetic air conditioning prototype - Guilherme F. Peixer; Anderson M. Lorenzoni; Yan C. Azeredo; Pedro M. Silva; Maria C.R. Silva; Gislaine Hoffmann; Diego dos Santos; Sergio L. Dutra; Gabriel M. do Rosário; Hígor F. Teza; Elias Pagnan; Rogério S. Sucaria; et al. (International Journal of Refrigeration, 2024)

Bioactivity of Prosopis alpataco and Prosopis flexuosa flours: Healthy alternatives as ingredients for nutritional foods - Elizabeth Hoffmann; Patricia Boeri; Romina Monasterio; Ariel Fontana; Maria Cecilia Puppo; Daniel Alejandro Barrio; Lucrecia Piñuel (Food Bioscience, 2024)

Factors Influencing Health-Related Quality of Life of Patients with Spinocerebellar Ataxia - Niklas Weber; Maresa Buchholz; Anika Rädke; Jennifer Faber; Tanja Schmitz-Hübsch; Heike Jacobi; Thomas Klockgether; Wolfgang Hoffmann; Bernhard Michalowsky; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; et al. (The Cerebellum, 2024)
Background Little is known about the progression of health-related quality of life (HRQoL) and predicting factors in spinocerebellar ataxia (SCA). Such knowledge is crucial to identify modifiable factors promoting everyday life with SCA and attenuating HRQoL decline. Objectives This study is to assess HRQoL progression and identify factors affecting SCA patients’ HRQoL. Methods Longitudinal data (three-year follow-up) of 310 SCA patients of the European SCA3/Machado-Joseph-Disease Initiative (ESMI) (2016-2022) and 525 SCA patients (SCA1, SCA2, SCA3 or SCA6) of the EUROSCA natural history study cohort (2006–2015) were assessed. Both large cohort studies share standardized assessments of clinical measures, SARA, INAS, PHQ-9, and HRQoL (EQ-5D-3L). The association between HRQoL and clinical measures was assessed by Spearman Correlation (r s ). Multivariable panel regression models were performed to evaluate the impact of patients’ socio-demographics, age of onset, SCA type and body mass index (BMI), and clinical measures on HRQoL progression. Results HRQoL significantly decreased over one (− 0.014, p = 0.095), two (− 0.028, p = 0.003), and three years (− 0.032, p = 0.002). Ataxia severity and mental health strongly correlated with HRQoL (r s SARA = − 0.589; r s PHQ-9 = − 0.507). HRQoL more intensively declined in male (ß = − 0.024, p = 0.038) patients with an earlier age of onset (ß = 0.002, p = 0.058). Higher progression of ataxia severity (ß = − 0.010, p ≤ 0.001), mental health problems (ß = − 0.012, p < 0.001), and higher BMI (ß = − 0.003, p = 0.029) caused more severe decline of patients’ HRQoL over time. Discussion In absence of curative treatments, stronger focus on mental health and weight influence could help clinical evaluation and accompany treatment improving SCA patients’ HRQoL, especially in male patients with early disease onset.

Effects of mineral and vitamin supplementation on pregnancy rates in Nelore cattle submitted to FTAI programs with different reactivity scores - Milton Maturana Filho; Barbara Piffero Mello; Kleber Menegon Lemes; Reuel Luiz Gonçalvez; João Paulo Mendes Lollato; Guilherme Pugliesi; Ed Hoffmann Madureira; Angela Gonella-Diaza; Claudia Maria Bertan Membrive (Livestock Science, 2024)

Use of monosodium glutamate as alternative to reduce sodium in cooking affects the physicochemical, phytochemical, and sensory attributes of pigmented and non-pigmented rice - Maria Antônia Fagundes De Leon; Lázaro da Costa Corrêa Cañizares; Betina Bueno Peres; Newiton da Silva Timm; Silvia Leticia Rivero Meza; Jessica Fernanda Hoffmann; Cristiano Dietrich Ferreira; Mauricio de Oliveira (International Journal of Gastronomy and Food Science, 2023)

Airborne pollen grain detection from partially labelled data utilising semi-supervised learning - Benjamin Jin; Manuel Milling; Maria Pilar Plaza; Jens O. Brunner; Claudia Traidl-Hoffmann; Björn W. Schuller; Athanasios Damialis (Science of The Total Environment, 2023)

Pollen long-distance transport associated with symptoms in pollen allergics on the German Alps: An old story with a new ending? - Daniela Bayr; Maria P. Plaza; Stefanie Gilles; Franziska Kolek; Vivien Leier-Wirtz; Claudia Traidl-Hoffmann; Athanasios Damialis (Science of The Total Environment, 2023)

Dopamine agonists pramipexole, ropinirole and rotigotine for the treatment of restless legs syndrome in pregnancy - Wolfgang E. Paulus; Eva-Maria Mair; Ulrike Friebe-Hoffmann (Neurotoxicology and Teratology, 2023)

A magnetocaloric air-conditioning system prototype - Guilherme F. Peixer; Maria C.R. Silva; Anderson Lorenzoni; Gislaine Hoffmann; Diego dos Santos; Gabriel M. do Rosário; Elias Pagnan; Hígor F. Teza; Pedro M. Silva; Sergio L. Dutra; Marcelo C. Ribeiro; Marcelo A.A. Rosa; et al. (International Journal of Refrigeration, 2023)

Betula pendula trees infected by birch idaeovirus and cherry leaf roll virus: Impacts of urbanisation and NO2 levels - Stefanie Gilles; Meike Meinzer; Maria Landgraf; Franziska Kolek; Susanne von Bargen; Kaja Pack; Athanasios Charalampopoulos; Surendra Ranpal; Daria Luschkova; Claudia Traidl-Hoffmann; Susanne Jochner-Oette; Athanasios Damialis; et al. (Environmental Pollution, 2023)

Pollen production of downy birch (Betula pubescens Ehrh.) along an altitudinal gradient in the European Alps - Surendra Ranpal; Susanne von Bargen; Stefanie Gilles; Daria Luschkova; Maria Landgraf; Claudia Traidl-Hoffmann; Carmen Büttner; Athanasios Damialis; Susanne Jochner-Oette (International Journal of Biometeorology, 2023)
High-altitude environments are highly susceptible to the effects of climate change. Thus, it is crucial to examine and understand the behaviour of specific plant traits along altitudinal gradients, which offer a real-life laboratory for analysing future impacts of climate change. The available information on how pollen production varies at different altitudes in mountainous areas is limited. In this study, we investigated pollen production of 17 birch ( Betula pubescens Ehrh.) individuals along an altitudinal gradient in the European Alps. We sampled catkins at nine locations in the years 2020–2021 and monitored air temperatures. We investigated how birch pollen, flowers and inflorescences are produced in relation to thermal factors at various elevations. We found that mean pollen production of Betula pubescens Ehrh. varied between 0.4 and 8.3 million pollen grains per catkin. We did not observe any significant relationships between the studied reproductive metrics and altitude. However, minimum temperature of the previous summer was found to be significantly correlated to pollen ( r s = 0.504, p = 0.039), flower ( r s = 0.613, p = 0.009) and catkin ( r s = 0.642, p = 0.005) production per volume unit of crown. Therefore, we suggest that temperature variability even at such small scales is very important for studying the response related to pollen production.

Mitochondrial dysfunction, oxidative stress, ER stress and mitochondria-ER crosstalk alterations in a chemical rat model of Huntington's disease: Potential benefits of bezafibrate - Morgana Brondani; Ana Cristina Roginski; Rafael Teixeira Ribeiro; Maria Paula de Medeiros; Chrístofer Ian Hernandez Hoffmann; Moacir Wajner; Guilhian Leipnitz; Bianca Seminotti (Toxicology Letters, 2023)

Levosimendan increases the phosphorylation state of phospholamban in the isolated human atrium - Lina Maria Rayo Abella; Robert Hoffmann; Joachim Neumann; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Levosimendan (up to 10 µM) given alone failed to increase force of contraction in isolated electrically stimulated (1 Hz) left atrial (LA) preparations from wild-type mice. Only in the additional presence of 0.1 µM rolipram, an inhibitor of the activity of phosphodiesterase IV, levosimendan increased force of contraction in LA and increased the phosphorylation state of phospholamban at amino acid serine 16. Levosimendan alone increased the beating rate in isolated spontaneously beating right atrial preparations from mice and this effect was potentiated by rolipram. The positive inotropic and the positive chronotropic effects of levosimendan in mouse atrial preparations were attenuated by 10 µM propranolol. Finally, we studied the contractile effects of levosimendan in isolated electrically stimulated (1 Hz) right atrial preparations from the human atrium (HAP), obtained during cardiac surgery. We detected concentration-dependent positive inotropic effects of levosimendan alone that reached plateau at 1 µM levosimendan in HAP ( n = 11). Levosimendan shortened time of tension relaxation in HAP. Cilostamide (1 µM), an inhibitor of phosphodiesterase III, or propranolol (10 µM) blocked the positive inotropic effect of levosimendan in HAP. Levosimendan (1 µM) alone increased in HAP the phosphorylation state of phospholamban. In conclusion, we present evidence that levosimendan acts via phosphodiesterase III inhibition in the human atrium leading to phospholamban phosphorylation and thus explaining the positive inotropic effects of levosimendan in HAP.

Local management and landscape composition affect predatory mites in European wine-growing regions - Stefan Möth; Sylvie Richart-Cervera; Maria Comsa; Rafael Alcalá Herrera; Christoph Hoffmann; Sebastian Kolb; Daniela Popescu; Jo Marie Reiff; Adrien Rusch; Pauline Tolle; Andreas Walzer; Silvia Winter (Agriculture, Ecosystems & Environment, 2023)

Heterogeneity on the abyssal plains: A case study in the Bering Sea - Julia D. Sigwart; Angelika Brandt; Davide Di Franco; Elva Escobar Briones; Sarah Gerken; Andrew J. Gooday; Candace J. Grimes; Kamila Głuchowska; Sven Hoffmann; Anna Maria Jażdżewska; Elham Kamyab; Andreas Kelch; et al. (Frontiers in Marine Science, 2023)
The abyssal plains are vast areas without large scale relief that occupy much of the ocean floor. Although long considered relatively featureless, they are now known to display substantial biological heterogeneity across different spatial scales. Ecological research in these regions benefits increasingly from non-destructive visual sampling of epifaunal organisms with imaging technology. We analysed images from ultra-high-definition towed camera transects at depths of around 3500 m across three stations (100–130 km apart) in the Bering Sea, to ask whether the density and distribution of visible epifauna indicated any substantial heterogeneity. We identified 71 different megafaunal taxa, of which 24 occurred at only one station. Measurements of the two most abundant faunal elements, the holothurian Elpidia minutissima and two xenophyophores morphotypes (the more common identifiable as Syringammina limosa ), indicated significant differences in local densities and patchy aggregations that were strikingly dissimilar among stations. One station was dominated by xenophyophores, one was relatively depauperate in both target taxa as well as other identified megafauna, and the third station was dominated by Elpidia . This is an unexpected level of variation within comparable transects in a well-mixed oceanic basin, reinforcing the emerging view that abyssal habitats encompass biological heterogeneity at similar spatial scales to terrestrial continental realms.

Screening of new adsorbents to remove algal organic matter from aqueous solutions: kinetic analyses and reduction of disinfection by-products formation - Luan de Souza Leite; Maria Teresa Hoffmann; Fábio Simões de Vicente; Danilo Vitorino dos Santos; Alexandre Mesquita; Felipe Bonganhi Juliato; Luiz Antonio Daniel (Environmental Science and Pollution Research, 2023)

The serotonin receptor 3E variant is a risk factor for female IBS-D - Nikola Fritz; Sabrina Berens; Yuanjun Dong; Cristina Martínez; Stefanie Schmitteckert; Lesley A. Houghton; Miriam Goebel-Stengel; Verena Wahl; Maria Kabisch; Dorothea Götze; Mauro D’Amato; Tenghao Zheng; et al. (Journal of Molecular Medicine, 2022)
Irritable bowel syndrome (IBS) is a gut-brain disorder of multifactorial origin. Evidence of disturbed serotonergic function in IBS accumulated for the 5-HT 3 receptor family. 5-HT 3 Rs are encoded by HTR3 genes and control GI function, and peristalsis and secretion, in particular. Moreover, 5-HT 3 R antagonists are beneficial in the treatment of diarrhea predominant IBS (IBS-D). We previously reported on functionally relevant SNPs in HTR3A c.-42C > T (rs1062613), HTR3C p.N163K (rs6766410), and HTR3E c.*76G > A (rs56109847 = rs62625044) being associated with IBS-D, and the HTR3B variant p.Y129S (rs1176744) was also described within the context of IBS. We performed a multi-center study to validate previous results and provide further evidence for the relevance of HTR3 genes in IBS pathogenesis. Therefore, genotype data of 2682 IBS patients and 9650 controls from 14 cohorts (Chile, Germany (2), Greece, Ireland, Spain, Sweden (2), the UK (3), and the USA (3)) were taken into account. Subsequent meta-analysis confirmed HTR3E c.*76G > A (rs56109847 = rs62625044) to be associated with female IBS-D (OR = 1.58; 95% CI (1.18, 2.12)). Complementary expression studies of four GI regions (jejunum, ileum, colon, sigmoid colon) of 66 IBS patients and 42 controls revealed only HTR3E to be robustly expressed. On top, HTR3E transcript levels were significantly reduced in the sigma of IBS patients ( p = 0.0187); more specifically, in those diagnosed with IBS-D ( p = 0.0145). In conclusion, meta-analysis confirmed rs56109847 = rs62625044 as a risk factor for female IBS-D. Expression analysis revealed reduced HTR3E levels in the sigmoid colon of IBS-D patients, which underlines the relevance of HTR3E in the pathogenesis of IBS-D.

Compound impact of land use and extreme climate on the 2020 fire record of the Brazilian Pantanal - Maria Lucia Ferreira Barbosa; Isadora Haddad; Ana Lucia da Silva Nascimento; Gabriel Máximo da Silva; Renata Moura da Veiga; Tânia Beatriz Hoffmann; Anielli Rosane de Souza; Ricardo Dalagnol; Annia Susin Streher; Francisca R. Souza Pereira; Luiz Eduardo Oliveira e Cruz de Aragão; Liana Oighenstein Anderson (Global Ecology and Biogeography, 2022)
Aim Our aim was to quantify the influence of climate and land use on major fires that occurred during the 2020 drought over the Brazilian Pantanal region. Location Alto Paraguay Basin, central‐western flank of Brazil. Time period 2003–2020. Methods We calculated climatic and burned area anomalies and Spearman's correlation between precipitation and sea surface temperature (SST). We assessed water coverage to identify the impact of the 2020 drought. We produced fire recurrence maps, identified the areas that burned for the first time in 2020, and estimated the carbon loss. Lastly, we assessed the burned areas within land‐use classes and land tenure. Results The anomalies showed that climatic variables in 2020 had an atypical behaviour, being hotter and drier than the historical average. The water surface area in the Pantanal has been decreasing annually from 2003, and in 2020 the reduction was 34% greater than the annual average. Burned areas in 2020 were 200% greater than the long‐term average, and 35% of the burned areas occurred for the first time in this year. We showed that 84% of these new fires occurred within natural vegetation, with 39% of the burned areas occurring in forests, an increase of 514%. Forest fires were responsible for 47% of the carbon loss in 2020. Finally, 70% of the fires in 2020 occurred within rural properties, 5% in indigenous lands and 10% in protected areas. Main conclusions The unprecedented fires in 2020 were not only a result of atypical climate, but also a consequence of the intensification of fire‐related human activities. Rural properties play a major role in Pantanal fires, requiring law enforcement and a consistent plan for increasing the protection of the conservation areas. We argue that ineffective fire prevention and the lack of suppression strategies were also key in enhancing the magnitude of these fires.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Secondary metabolite contents in different parts of cassava plants infested by Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) - Diego Gazola; Claudemir Zucareli; Rudiney Ringenberg; Maria Cristina Neves de Oliveira; José Perez da Graça; Estela de Oliveira Nunes; Clara Beatriz Hoffmann-Campo (Arthropod-Plant Interactions, 2019)

Mesenchymal Stem Cells Form 3D Clusters Following Intraventricular Transplantation - Nicole Jungwirth; Laura Salinas Tejedor; Wen Jin; Viktoria Gudi; Thomas Skripuletz; Veronika Maria Stein; Andrea Tipold; Andrea Hoffmann; Martin Stangel; Wolfgang Baumgärtner; Florian Hansmann (Journal of Molecular Neuroscience, 2018)

Permanent Cerebellar Degeneration After Acute Hyperthermia with Non-toxic Lithium Levels: a Case Report and Review of Literature - Fabian H. Rossi; Elisa Marie Rossi; Michael Hoffmann; Welwin Liu; Ramon Rodriguez Cruz; Natasha Antonovich; Arash Rezaei; Elizabeth Gonzalez; Maria Clara Franco; Alvaro Estevez; Florian Thomas (The Cerebellum, 2017)

Immune Modulation and Prevention of Autoimmune Disease by Repeated Sequences from Parasites Linked to Self Antigens - Fabiola Puentes; Katharina Dickhaut; Maria Hofstätter; Jennifer Pfeil; Uta Lauer; Alf Hamann; Ute Hoffmann; Kirsten Falk; Olaf Rötzschke (Journal of Neuroimmune Pharmacology, 2016)

Biological aspects of Bemisia tabaci biotype B and the chemical causes of resistance in soybean genotypes - Simone S. Vieira; André L. Lourenção; José P. da Graça; Tatiani Janegitz; Mariana C. Salvador; Maria Cristina N. de Oliveira; Clara Beatriz Hoffmann-Campo (Arthropod-Plant Interactions, 2016)

European Marine Biodiversity Monitoring Networks: Strengths, Weaknesses, Opportunities and Threats - Joana Patrício; Sally Little; Krysia Mazik; Konstantia-Nadia Papadopoulou; Christopher J. Smith; Heliana Teixeira; Helene Hoffmann; Maria C. Uyarra; Oihana Solaun; Argyro Zenetos; Gokhan Kaboglu; Olga Kryvenko; et al. (Frontiers in Marine Science, 2016)

Species cross-amplification, identification and genetic variation of 17 species of deer (Cervidae) with microsatellite and mitochondrial DNA from antlers - G. Sebastian Hoffmann; Jes Johannesen; Eva Maria Griebeler (Molecular Biology Reports, 2015)

Crosslinking EEG time–frequency decomposition and fMRI in error monitoring - Sven Hoffmann; Franziska Labrenz; Maria Themann; Edmund Wascher; Christian Beste (Brain Structure and Function, 2014)

Ecological assessment of Portuguese reservoirs based on littoral epilithic diatoms - Maria Helena Novais; Saúl Blanco; Cristina Delgado; Manuela Morais; Lucien Hoffmann; Luc Ector (Hydrobiologia, 2012)

Genome‐wide single nucleotide polymorphisms reveal population history and adaptive divergence in wild guppies - EVA‐MARIA WILLING; PAUL BENTZEN; COCK Van OOSTERHOUT; MARGARETE HOFFMANN; JOANNE CABLE; FELIX BREDEN; DETLEF WEIGEL; CHRISTINE DREYER (Molecular Ecology, 2010)
Adaptation of guppies ( Poecilia reticulata ) to contrasting upland and lowland habitats has been extensively studied with respect to behaviour, morphology and life history traits. Yet population history has not been studied at the whole‐genome level. Although single nucleotide polymorphisms (SNPs) are the most abundant form of variation in many genomes and consequently very informative for a genome‐wide picture of standing natural variation in populations, genome‐wide SNP data are rarely available for wild vertebrates. Here we use genetically mapped SNP markers to comprehensively survey genetic variation within and among naturally occurring guppy populations from a wide geographic range in Trinidad and Venezuela. Results from three different clustering methods, Neighbor‐net, principal component analysis (PCA) and Bayesian analysis show that the population substructure agrees with geographic separation and largely with previously hypothesized patterns of historical colonization. Within major drainages (Caroni, Oropouche and Northern), populations are genetically similar, but those in different geographic regions are highly divergent from one another, with some indications of ancient shared polymorphisms. Clear genomic signatures of a previous introduction experiment were seen, and we detected additional potential admixture events. Headwater populations were significantly less heterozygous than downstream populations. Pairwise F ST values revealed marked differences in allele frequencies among populations from different regions, and also among populations within the same region. F ST outlier methods indicated some regions of the genome as being under directional selection. Overall, this study demonstrates the power of a genome‐wide SNP data set to inform for studies on natural variation, adaptation and evolution of wild populations

Revision of the genus Leptopus (Phyllanthaceae, Euphorbiaceae sensu lato) - Maria S. Vorontsova; Petra Hoffmann (Kew Bulletin, 2009)

Purification of Candida guilliermondii and Pichia ohmeri killer toxin as an active agent against Penicillium expansum - Alexandre Rodrigo Coelho; Masahico Tachi; Fernando Carlos Pagnocca; Gisele Maria Andrade Nobrega; Fernando Leite Hoffmann; Ken-ichi Harada; Elisa Yoko Hirooka (Food Additives & Contaminants: Part A, 2009)

Genomic characterization of a novel group A lamb rotavirus isolated in Zaragoza, Spain - Max Ciarlet; Christian Hoffmann; Eleonora Lorusso; Rafael Baselga; Maria Assunta Cafiero; Krisztián Bányai; Jelle Matthijnssens; Viviana Parreño; Simona de Grazia; Canio Buonavoglia; Vito Martella (Virus Genes, 2008)

A phylogenetic classification of tribe Poranthereae (Phyllanthaceae, Euphorbiaceae sensu lato) - Maria S. Vorontsova; Petra Hoffmann (Kew Bulletin, 2008)

Roles of Na+/H+ exchange in regulation of p38 mitogen-activated protein kinase activity and cell death after chemical anoxia in NIH3T3 fibroblasts - Maria L. Rentsch; Carlo G. Ossum; Else K. Hoffmann; Stine F. Pedersen (Pflügers Archiv - European Journal of Physiology, 2007)

Alpha1-antitrypsin heterozygosity plays a positive role in attainment of longevity - Florinda Listì; Giuseppina Candore; Maria Paola Grimaldi; Domenico Lio; Giuseppina Colonna-Romano; Valentina Orlando; Marco Caruso; Enrico Hoffmann; Giuseppe Paolisso; Claudio Franceschi; Calogero Caruso (Biogerontology, 2007)

Intake of fruits and vegetables and risk of cancer of the upper aero-digestive tract: the prospective EPIC-study - Heiner Boeing; Thomas Dietrich; Kurt Hoffmann; Tobias Pischon; Pietro Ferrari; Petra H. Lahmann; Marie Christine Boutron-Ruault; Francoise Clavel-Chapelon; Naomi Allen; Tim Key; Guri Skeie; Eiliv Lund; et al. (Cancer Causes & Control, 2006)

Are Chemical Compounds Important for Soybean Resistance to Anticarsia gemmatalis? - Giorla Carla Piubelli; Clara Beatriz Hoffmann-Campo; Flávio Moscardi; Sandra Hitomi Miyakubo; Maria Cristina Neves De Oliveira (Journal of Chemical Ecology, 2005)